Development of Augmented Reality Learning Media for Plantae Material in Class X Biology Subjects Using Arttoolkit - Yoga Putra Jaya; Agus Efendi; Endar Suprih Wihidayat (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2023)
A lot of material discusses Plantae, so interesting learning is needed so that students can easily accept and understand the material provided. AR technology can facilitate learning Plantae in the classroom. This research develops AR-based